Beckman Paragon CZE 2000 Capillary Electrophoresis System (1990)
Beckman's Paragon line of electrophoresis systems debuted in 1981. The CZE 2000 was released in 1993.
Keywords: Scientific apparatus and instruments; Capillary electrophoresis; Beckman Instruments, Inc.